Stability of the spray-dried pigment of red dragon fruit [Hylocereus polyrhizus (Weber) Britton and Rose] as a function of organic acid additives and storage conditions - Woo, K. K.; Fanny Wong, F. N.; Chatherine Chua, H. S.; Tang, P. Y. (2011)
This study evaluated the effect of organic acid additives, temperature and illumination on the color retention of the spray-dried red violet pigment of red dragon fruit (Hylocereus polyrhizus [Weber] Britton and Rose) during storage. The pigment was extracted using distilled water at a ratio of 1:1. It was then filtered through a press filter to remove unwanted juice matrix. The collected pigment was subsequently treated with either 0.1% (w/v) ascorbic acid or 0.1% (w/v) citric acid prior to spray-drying procedure. Pigment without additives was used as the control. The resulting spray-dried product was stored at 25 °C and 4 °C, with or without illumination, and at -20 °C without illumination. Quantitative color analysis (L*, C* and h° value) of the spray-dried pigment was carried out within 6 wk. Color regeneration (approximately 20-40% of the initial) was observed at the end of week 5 in all control samples stored in the dark (25 °C, 4 °C and -20 °C). Quantitative determination showed that the h° value shifted from blue (226) to red zone (345) after 6 wk. Increase in C*values was observed in most of the treatments. However, L* did not show significant (P>0.05) changes throughout the storage period. Ascorbic acid and citric acid did not delay color degradation.
Keywords: Dragon fruit; Plant pigments